2009
DOI: 10.1159/000232161
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Effects of Triiodothyronine on the Osteogenic Differentiation of Rat Bone Marrow Mesenchymal Stem Cells

Abstract: Background/Aims: The aim of this study was to investigate the dose-dependent effects of triiodothyronine (T3) on the osteogenic differentiation of mesenchymal stem cells(MSCs). Methods: MSCs that express CD73, CD54 (intercellular adhesion molecule-1) and CD90 were cultured in triplicate (1 × 105/well) in osteogenic medium with T3 (1, 10, 103 or 105 pM) or without T3 (control) for 7, 14 and 21 days. Alkaline phosphatase activity, conversion of MTT into formazan crystals, collage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 64 publications
2
27
0
8
Order By: Relevance
“…This finding was described in adults rats with hyperthyroidism (14). According to some researchers, thyroid hormones stimulate osteoblast synthesis and, thus, the voluminous aspect observed in the osteoblasts of offspring of rats treated with thyroxin may be a reflex of this action (30,31). Besides, a recent study demonstrated that stem cells of the bone marrow of hyperthyroid female rats show greater potential for differentiation in osteoblasts (31), justifying the presence of areas of hyperplasia and the consequent increase in the percentage of trabecular bone tissue observed in animals in this study.…”
Section: Discussionmentioning
confidence: 79%
“…This finding was described in adults rats with hyperthyroidism (14). According to some researchers, thyroid hormones stimulate osteoblast synthesis and, thus, the voluminous aspect observed in the osteoblasts of offspring of rats treated with thyroxin may be a reflex of this action (30,31). Besides, a recent study demonstrated that stem cells of the bone marrow of hyperthyroid female rats show greater potential for differentiation in osteoblasts (31), justifying the presence of areas of hyperplasia and the consequent increase in the percentage of trabecular bone tissue observed in animals in this study.…”
Section: Discussionmentioning
confidence: 79%
“…Posteriomente, foram adicionados 300mL de NaOH 0,5M e a placa foi incubada por mais 30 minutos. Em seguida, 100mL de cada poço foram transferidos para placas de 96 poços para leitura em espectrofotômetro com comprimento de onda de 540nm de acordo com Boeloni et al (2009).…”
Section: Síntese De Colágeno Porcentagem De Células E De Matriz Mineunclassified
“…Esses fatores são representados por fatores de transcrição gênica e de crescimento, citocinas, densidade celular, contato físico com as células vizinhas, estímulo físico (2,3) e mecânico (2-4) e por hormônios representados pelo estrógeno, glicocorticoides, vitamina D, leptina e pelos hormônios tireoidianos (5)(6)(7)(8)(9)(10).…”
Section: Introductionunclassified
“…Resultados recentes demonstram que a adição de triiodotironina (T3) in vitro aumenta a diferenciação osteogênica das CTM-MO de ratas jovens saudáveis (8,10) e também de ratas com osteoporose (17). No entanto, ainda não se sabe qual o efeito da T3 na redução da diferenciação osteogênica de CTM-MO decorrente da idade.…”
Section: Introductionunclassified